The Effect of Environmental, Social, and Governance (ESG) Disclosure on Market Value With Company Financial Performance As A Mediatıng Variable (Case Study of Banking Sector Companies Listed on The Indonesia Stock Exchange for the Period 2019-2023) - Khotimah, Siti; Maryani, Neni (CV. Proaksara Global Transeduka, 2025)
The increase in awareness of environmental, social, and governance (ESG) factors is prompting companies to incorporate ESG principles into their business practices, especially in the banking industry, which plays a crucial role in the financial system. This research seeks to explore how ESG disclosure affects a company's market worth, with financial performance acting as a key mediator. The inspiration for this study arises from contradictory results regarding the relationship between ESG and market value in the Indonesian banking sector. In this research, a quantitative method was employed to examine data from the annual and sustainability reports of banking institutions listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. The researchers carefully selected their sample using a specific technique and ended up with 44 data points to analyse after removing any outliers. They utilised the Global Reporting Initiative (GRI) guidelines to evaluate ESG disclosure, Tobin's Q to estimate market value, and Return on Assets (ROA) to measure financial performance. The study included the use of simple linear regression and the Sobel test for mediation analysis. The results of their study indicated that ESG disclosure has a significant, positive effect on both market value and financial performance. Moreover, financial performance was found to positively influence market value and act as a mediator in the link between ESG disclosure and market value. These findings suggest that effective ESG disclosure can boost investor confidence by improving financial performance, ultimately leading to a positive impact on the company's market value.